Participatory Integrated Climate Services for Agriculture (PICSA) Intermediary Training, Dodoma, Tanzania - Mwanga, Sixbert; Kisanga, Juvenal; Dinh, Dannie (2017)
Since 2014, World Food Programme (WFP), CGIAR Research Program Climate Change Agriculture and Food Security (CCAFS), Tanzania Meteorological Agency (TMA) and University of Reading (UoR) have been hosting trainings of extension workers—or, intermediaries—and sharing climate information services. An intensive five-day training on Participatory Integrated Climate Services for Agriculture (PICSA) approach was held September 7-11, 2015 in Dodoma, Tanzania to equip Dodoma district intermediaries with the capacity to provide farmers with locally relevant climate, crop and livelihood information. About 42 intermediaries from the Prime Minsters’ Regional Administrative Office, local government, and Tanzania Red Cross Society were trained on a number of areas from PICSA field manual and other topics, such as integrating participatory decision-making tools under different weather conditions and seasonal and short-term climate forecast. Through the training, all intermediaries were able to make interpretation and opt for best option based on local seasonal forecast. For effective implementation of PICSA Process at local levels, training participants formulated work plans and shared copy with facilitators and district supervisors for close follow-up. All trained intermediaries also received a special assessment form to distribute to farmers to complete at the end of the season. A one-day farmer training workshop immediately followed, offering the freshly trained intermediaries an opportunity to learn by doing.